Gender and skill-level differences in visual search strategies among basketball athletes: insights from eye-tracking analysis - Yu, H.; Gai, B. (International Journal of Sport and Exercise Psychology, 2025)
Visual search efficiency plays a critical role in fast-paced sports like basketball, where athletes must rapidly extract and respond to key visual cues. This study investigated how gender and skill level influence visual search strategies using eye-tracking analysis during basketball decision-making tasks. Forty participants (10 high-level male athletes, 10 high-level female athletes, 10 untrained male students, and 10 untrained female students) were recruited and assigned to four groups based on gender and expertise. Participants viewed static image sequences extracted from professional basketball game videos, depicting offensive scenarios with varying visual complexity. Task complexity was manipulated by the number of players in each image: simple scenes (=5 players) and complex scenes (>5 players). Participants made real-time decisions (shoot, dribble, or pass), while performance metrics (accuracy, reaction time) and eye-tracking indicators (fixation count, duration, frequency, and gaze trajectory) were recorded. A 2 × 2 × 2 ANOVA revealed that athletes outperformed non-athletes across most measures, particularly in complex tasks. High-level female athletes demonstrated the highest accuracy and fastest reaction times, despite exhibiting longer fixation durations. Male athletes showed fewer fixations and lower fixation frequencies, indicating more economical visual scanning. Gaze heatmaps and trajectory plots illustrated more concentrated and task-relevant fixations among expert groups. Feature engineering further identified fixation duration and frequency as the most discriminative indicators of expertise. These findings highlight the interactive effects of gender, expertise, and task complexity on visual-cognitive performance and suggest that targeted training based on eye-movement metrics may enhance decision-making efficiency in basketball.